Polideportivo urbano El Lago (2016)
"The proposed use of my project is that of a sports center, which has an urban condition, it is mean that there are restrictions in the area of occupancy area but not height due to its location. A sports center is understood as a place where several continuous and moving activities of an extroverted and non-introverted character meet. It is part of a first condition of the place where the needs that the project requires are high, that is why in principle all activities are concentrated in a single container. As a result of the activities that are generated in the interior, the project has a characteristic of transparency that allows the visual and physical relations of both the project to the city and the city to the project." -- Tomado del Formato de Documento de Grado